Phytochemical analysis and green synthesis of silver nanoparticles using Clerodendrum infortunatum L. for potential antibacterial applications - Karn, Saraswati; Budha Magar, Akash; Pathak, Ishwor; Sharma, Khaga Raj (Scientific World, 2025)
Clerodendrum infortunatum L. is a traditional medicinal plant used to treat various illnesses since ancient times by traditional healers of the Terai region of Nepal. The present study performed qualitative and quantitative phytochemical analysis and investigation of the antioxidant and antibacterial activities of five different solvent extracts of root, stem, and leaf. In addition, silver nanoparticles were synthesized using root aqueous extract of the plant. The methanolic extract of root contained the highest TPC and TFC values of 26.18±3.83 mg GAE/g and 7.2±1.2 mg QE/g respectively. The methanolic extract of the leaf also showed the highest DPPH radical scavenging activity with an IC50 of 59.96 μg/mL. In the antibacterial assay, the aqueous extract of leaf and stem showed strong antibacterial properties against Escherichia coli with ZOI values of 19 mm and 18 mm respectively which was more than the ZOI value of the positive control neomycin (16 mm). The aqueous root extract was successfully used in the green synthesis of silver nanoparticles. The synthesized silver nanoparticle displayed an SPR peak at 407 nm. The average diameter of nanoparticles was calculated as 11.82 nm using the Debye-Scherer equation. They were characterized using different spectroscopic techniques. Synthesized nanoparticles showed comparatively more activity against gram-negative Klebsiella pneumoniae than gram-positive Staphylococcus aureus. In conclusion, the plant is rich in phytochemicals with potent antibacterial activity. It can be effectively used in the green synthesis of nanoparticles.